Mobibike application for android - Nur Syafikah Nabilla, Zaharuddin (2015)
Third world countries have witnessed many technologies development and achievement which leads to competition among many countries to adapt with this kind of trend. In Malaysia, majority of road users are those who have a four-wheel drive. Thus, technology implemented and enhanced is more on ensuring their comfort during using the road without acknowledging the rights of minority user which are the cyclist. MobiBike is an application that use smart phone device that works as a medium of turning on and turning off the signal lamp, view the bike's speed and distance traveled by user. This application is being developed in order to maximize the sense of security among cyclist, to pay more attention to the rights of cyclist and to add more facilities and equipment for cyclists. In future, this application is expected to be expanded and fully utilized by cyclists especially. The study use Extreme Programming method because it focuses on customer satisfaction where the developers are capable on responding to frequent changes on user requirement and easy to fix any issues for each version. Finally, the application is tested and the result confirms that the proposed system is capable to comply with the research objectives.